Penerapan CLT dalam pengajaran Bahasa Arab di sekolah SMa Nurul huda - Lathifatul Qolbi; Moh. Syaifudin (Program Studi Pendidikan Bahasa Arab Sekolah Tinggi Bahasa Arab dan Dakwah Masjid Agung Sunan Ampel Surabaya, 2024)
The Communicative Language Teaching (CLT) approach has been implemented in Arabic language teaching at Nurul Huda High School with the aim of enhancing students' effective communication skills. This method emphasizes the importance of using language in real-life contexts, integrating speaking, listening, reading, and writing skills in a balanced manner. The implementation of CLT involves various interactive activities such as role-playing, group discussions, and simulations of daily conversations designed to create a dynamic and engaging learning environment. As a result, students have shown significant improvement in their communication skills in Arabic, as well as a better understanding of the cultural and social contexts related to the language. The application of CLT at Nurul Huda High School also encourages active student participation and increases their motivation to learn, making Arabic language learning more relevant and applicable in daily life.